Automated system for collection and differentiated evaluation of functional and special physical fitness of swimmers of different level of qualifications - Solopov I.N.,; Fomichenko T.G.,; Avdienko V.B.,; Bgantseva I.V., (Theory and Practice of Physical Culture, 2024)
Objective of the study was to justify and develop an automated system for collecting and differentiated assessment of functional and special physical fitness of swimmers of different skill levels. Methods and structure of the study. The analysis of scientific and methodological literature and practical experience of leading trainers; methods of experimental diagnostics of special physical and functional fitness of swimmers of both sexes, different qualifications and different swimming methods; the method of logical design. Results and conclusions. The structure of an automated system consists of a «manual processes» component and an «automatic processes» component. The «manual processes» component combines the process of differentiated diagnostics of swimmers level of readiness and the process of data entry. The «automated processes» component combines a number of procedural actions carried out using specialized computer software: normalization of all entered indicators (reduction to a single scale), differentiated assessment of each entered indicator, calculation of an integrative (average) assessment of the entire set of entered indicators, ranking and comparison of assessments of individual indicators, ranking and comparison of integrative assessments, visualization of assessments of all modalities, collection and archiving of information in a data bank, issuance of information to users. It is noted that the automated system for collecting and differentiated assessment of swimmers preparedness allows, in remote access mode, to collect and differentiated assessment of the functional and special physical preparedness of swimmers of different skill levels.